Implementasi Program Generasi Berencana (GenRe) di Kelurahan Tegal Rejo Kecamatan Medan Perjuangan - Nurul Ufa Nainggolan; Masitho Batubara; Agung Suharyanto (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2022)
The Planning Generation Program is government strategy to overcome development problems, sepecially adolescents. The phenomenon in this study is the lack of supervision and parental assertiveness in educating children which is a factor in the occurence of deviant behavior. This research aim determine the Implementation of the Generation Planning Program (GenRe) and the obtacles in the Implementation of the GenRe Program in Tegal Rejo Village Medan Perjuangan District. This research uses descriptive qualitative research. Data were collected based on data collection techniques, namely observation, interview, documentation and tringgular data. The Implementation of the GenRe Program In Tegal Rejo Village is quite good but has not been effective int its application to adolescents seen from its indicators implementation, namely communication, resosurces, disposition and bureaucratic structure as well as obtacles to the Implementation of the GenRe Program In Tegal Rejo Village, Medan Perjuangan District, is that target location for their activities is due to the covid-19 outbreak and the lack of human resources/implenters in providing outreach to adolescents. GenRe trainers and managers must put more effort into disseminnating the GenRe program to adolescents so that the desired goals can be achieved.